1991
DOI: 10.1038/jcbfm.1991.107
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of the Human Blood-Brain Barrier Transport of Lactate and its Influence by Hypercapnia

Abstract: Summary: Blood-brain barrier permeability to L-Iactate was studied in 18 patients with the double indicator tech nique. Venous outflow curves were obtained during normo-and hypercapnia and were analyzed by means of a model that takes tracer backflux and capillary hetero geneity of transit times into account. The average unidi rectional extraction of L-Iactate was 15%; the transport from the blood to the brain (PS I ) was 0.081 ml g -I min-I and the transport from the brain to the blood (PS 2 ) was on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 14 publications
4
40
0
Order By: Relevance
“…Early work in anesthetized animals showed that lactate crosses the bloodbrain barrier by facilitated diffusion in a stereospecific and saturable manner, and the rate of lactate uptake is much lower than that of glucose (28). However, more recent studies in awake animals and humans demonstrated that the average brain uptake of lactate in resting brain is approximately seven times higher than previously calculated (28), reaching Ϸ50% of that of glucose (29,30). Although entry of lactate from plasma into resting brain is more rapid than previously thought (31), Lear and Kasliwal (32) have shown that the local transport of lactate is further increased during brain activation, which could lead to an increased effect of the injected lactate.…”
Section: Discussionmentioning
confidence: 92%
“…Early work in anesthetized animals showed that lactate crosses the bloodbrain barrier by facilitated diffusion in a stereospecific and saturable manner, and the rate of lactate uptake is much lower than that of glucose (28). However, more recent studies in awake animals and humans demonstrated that the average brain uptake of lactate in resting brain is approximately seven times higher than previously calculated (28), reaching Ϸ50% of that of glucose (29,30). Although entry of lactate from plasma into resting brain is more rapid than previously thought (31), Lear and Kasliwal (32) have shown that the local transport of lactate is further increased during brain activation, which could lead to an increased effect of the injected lactate.…”
Section: Discussionmentioning
confidence: 92%
“…Assuming a brain Lac concentration of 1 mmol/g, a pseudo first-order rate constant k Lac = 0.09 min À1 can be estimated from the reported exchange rate of 0.09 mmol/g/min (Knudsen et al, 1991). The maximal Lac efflux is thus k Lac * D[Lac] = 0.018 mmol/g/min, which corresponds to 8% of the increased Pyr derived from Glc.…”
Section: Discussionmentioning
confidence: 99%
“…This could be caused by inhibition of cerebral lactate uptake mediated by the increase in pH during hyperventilation. 33 However, increased outward flux compared with inward flux of lactate at the monocarboxylate carrier transport system cannot be excluded. In the present study, LOI decreased, but remained positive, indicating aerobic cerebral metabolism during short-term hyperventilation.…”
Section: Discussionmentioning
confidence: 99%